Case series of maternal mortality and maternal near miss due to severe acute respiratory syndrome coronavirus 2 - Vanremmawii; Lalrinfela; Lalduhchhungi; Harvey Vanlalpeka; Lalramhluna PC (Asian Journal of Medical Sciences, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) that causes the COVID-19 pandemic has affected every household of the remotest part of North East India, Mizoram. The pregnant women do not have a higher chance of getting infected, yet the infection seems to be more severe. We are reporting five cases of maternal death and two cases of maternal near miss in ZMC of Mizoram. Case 1 to 5 were maternal death due to COVID-19. All of them were multigravida within the age group of 27–41 years with a period of gestation 24–37 weeks. The presenting complaints were fever and cough more than 3 days with an investigation report revealing raised C-reactive protein (CRP) and severe pneumonia. Case 6 (Near miss) was 20 years, primigravida at term pregnancy in labor with a history of fever for 2 days with an investigation report revealing raised CRP and severe pneumonia, the baby was delivered asphyxiated and died. Case 7 (Near miss) was 17 years old primigravida at term pregnancy admitted as asymptomatic COVID-19 positive, elective caesarean section was done for Obstetrics indication, the patient later developed fever and moderate pneumonia on 5 days of hospitalization, she also developed eclampsia on 7th hospital day, she survived after intensive care in the intensive care unit.